A research report on status of hypertension and its associated factors in selected wards of Lalitpur metropolitan city. - Sharma,Praju (2018)
ABSTRACT: Introduction: Hypertension is well known to be a topic of concern internationally. It has highly affected both developed and non-developed countries of the world. It is also refers as a 'silent killer' disease, because it remains undetected unless the blood pressure is measured. Most of the hypertensive cases are stated to be detected when the blood pressure is checked when they suffer from other health problems. Objective: The objective of this study was to assess the status of hypertension and its associated factors in selected wards of Lalitpur Metropolitan City. Methodology:Cross sectional study design was used to conduct the study from Jestha 2075 to Ashad 2075. It was conducted in Lalitpur district of ward 16, 18, 20 and 21. The sample size of the research was 300, of age 40 years or more. The data were entered and analyzed in Epi Data version 3.1 and SPSS version 25 respectively. Results: The study included (50%) male and (50%) female respondents. Majority of the respondents (81.3%) were newars. The illiterate respondents were (23%). The unemployed respondents were found to be (20.3%). The mean age and SD of the respondents was found to be 57.06 years and 12.702 respectively. It was found that (28.3%) the respondents who measure their blood pressure regularly were found to have hypertension. Discussion: There is a huge variation in prevalence of hypertension all around the world. The studies have shown that people who were unemployed people were likely to suffer from hypertension. Over weighed people also have been reported to be hypertensive. It was also found that male and those who drink alcohol were likely to suffer from hypertension.However this study did not show any association of hypertension with sex and alcoholism. Conclusion:The study concluded (28.3%) subjects suffering from hypertension. Religion and occupation were statistically significant with hypertension in case of socio demographic characteristics. People who were over weighed were found twice likely to be hypertensive than those who are underweight. People with co-morbid diseases were reported to have the risk of hypertension by six times than those who do not. Keywords: Hypertension, BMI etc.